Spodbujanje kakovostnega odnosa med materjo in otrokom pri hranjenju od rojstva do osnovne šole - Gaber, Sandra (Obzornik zdravstvene nege, 2005)
ln the article, the author presents theoretical grounds on the basis of' literature survey in Slovenian and other languages on family dynamics and related to the nrocess of attachment among preschool children and parent/caretakers during feeding in different environments. The article presents the family and relations within it, the philosophy of family centerednursing care and the attachment process of mother and child in general. Feeding activities of preschool children and relations between them and their caretakers are presented in different environments-home, kindergarten and hospital. Literature survey going on from September 2003 until February 2004 included specialized databases and covered critical selection of theories and their presentation. The author's intention was to stress the need for the promotion of qualitative relatinus during feeding which is, according to her opinion, under estimated. At the same time, the author encourages nurses to start thinking about active planning and carrying out of quality relationships in general, and during feeding as well, vhich allleads to quality relations between parents/caretakers and children.
Keywords: Breast Feeding; Child; Child Nutrition; Dojenček, prehrana; Dojenje; Health Education; hranjenje; Infant Nutrition; Mati-otrok, odnosi; Mother-Child Relations; Nursing Care; otroci; Otrok; Otroška prehrana; prehranjevanje; starši; Zdravstvena nega; Zdravstvena vzgoja